Core-shell microencapsulation of hematopoietic stem cells for the optimisation of lentiviral gene delivery using microfluidics - Sun, Qinglu (Nanyang Technological University, 2024)
This project employed an aqueous two-phase system and double-emulsion method (water-in-water-in-oil) to synthesize microcapsules for encapsulation of hematopoietic stem cells (HSCs) and lentivirus (LVs) with a custom-made microfluidic platform, and the synthesis process was optimized. Two biocompatible materials dextran (DEX) and poly(ethylene glycol) (PEG) were selected as the shell and core phase respectively. Parameters (concentrations of solutions, flow rates, presence of surfactants) that may influence the microcapsules generation process were systematically examined for their effects on the structure and stability of microcapsules. In combination with in vitro testing for the cytotoxic effects of the selected core phase material PEG, study results indicate that 10wt% DEX and 5wt% PEG were able to produce the required core-shell structure with an average microcapsule diameter of 437.3 ± 8.77μm, while introducing minimal adverse effects on cell viability. An increase in microcapsule size and decrease in core size would occur when the relative flow rate between the shell and core phase was increased. Furthermore, it was found that the presence of surfactants in the continuous phase was not necessary during generation of microcapsules in the microfluidic device. To enhance the stability of the microcapsules, the DEX shell of the microcapsules was replaced by methacrylated DEX, which was photo-crosslinked via exposure to 405nm light with an intensity of 200mW/cm2 for 12s. This allowed microcapsules to retain their concentric core-shell structure for approximately 7 days. Cell viability assays indicate that this set of photo-crosslinking conditions is safe for cells. The microcapsules are intended to be used for high-throughput screening of transduction enhancers that can increase the efficiency of lentiviral transduction of HSCs.